Mental Health Consequences of Lockdown During the COVID-19 Pandemic: A Cross-Sectional Study - Msherghi, Ahmed; Alsuyihili, Ali; Alsoufi, Ahmed; Ashini, Aimen; Alkshik, Zenib; Alshareea, Entisar; Idheiraj, Hanadi; Nagib, Taha; Abusriwel, Munera; Mustafa, Nada; Mohammed, Fatima; Eshbeel, Ayah; et al. (Frontiers in Psychology, 2021)
Objective We aimed to provide an overview of the psychological status and behavioral consequences of the lockdown during the COVID-19 pandemic in Libya. Methods A cross-sectional study was conducted among the Libyan population through May and June 2020 in more than 20 cities. The survey comprised basic demographic data of the participants and anxiety symptoms measured using the seven-item Generalized Anxiety Disorder scale (GAD-7) with ≥15 as the cut-off score for clinically-significant anxiety symptoms. Additionally, a survey regarding the lockdown effect was administered, which consisted of several parts, to measure the lockdown status. Results A total of 8084 responses were recorded, of which, 5090 (63%) were women and 2994 (37%) were men. The mean age (SD) for study participants was 27.2 (8.9) years. Among the participants, 1145 (14.2%) reached the cut-off score to detect anxiety symptoms; however, of the study variables, only five were predictors of clinically-significant anxiety: age, gender, marital status, work status, being a financial supporter for the family, and being infected with COVID-19. Women had 1.19 times higher odds to exhibit anxiety symptoms than men. Increasing age was significantly associated with reduced likelihood of exhibiting anxiety symptoms, whereas being married was significantly associated with higher likelihood of anxiety symptoms, compared to not being married. Being suspended from work was associated with an increase in the likelihood of anxiety symptoms. However, we found that being infected with COVID-19 was associated with a 9.59 times higher risk of exhibiting severe anxiety symptoms. Among the study participants, 1451 (17.9%) reported a physical and/or verbal abuse episode from family members, 958 (11.9%) reported abuse outside the family, and 641 (7.9%) reported abuse from enforcers, during the lockdown. Conclusion Our study provided an overview of the psychological and behavioral status, among those who resided in Libya during the civil war and COVID-19 pandemic. The study demonstrates a concerningly high level of clinically-significant anxiety during lockdown among the Libyan population during Libya’s lockdown period.